ENVIRONMENTALLY ADJUSTED PRODUCTIVITY GROWTH OF INDONESIAN RICE PRODUCTION - Mariyono, Joko (Journal of Indonesian Economy and Business, 2013)
Productivity of Indonesian rice agriculture needs to grow substantially to ensure national food security. However, the environmental cost should be taken into account. Thisstudy aims to analyse productivity growth of rice by decomposing it into technological change, scale effects, allocative efficiency and technical efficiency. Environmental cost associated with the use of environmentally detrimental inputs is internalised to obtain environmentally adjusted productivity growth. The result indicates that total factorproductivity growth is driven by technological change and social efficiency effects.Environmentally adjusted productivity growth is less than conventional productivity growth. Some policies to increase the environmentally adjusted productivity growth areproposed.Keywords: internalizing environmental cost, total factor productivity, rice production, scale effect, efficiency.